ANÁLISE METODOLÓGICA DAS DISSERTAÇÕES DEFENDIDAS NO PROGRAMA DE PÓS-GRADUAÇÃO EM ADMINISTRAÇÃO DA UCS - Gabriela Zanandrea (Universidade Federal de Santa Catarina, 2017)
The present study comprises an investigation about the methodological research practices in Business Management. Therefore it has the goal to identify the methodological approaches taken in the dissertations of the Master's course of Business Management inside the Graduate Program in Business Management at the Caxias do Sul University. An exploratory/descriptive study was done, with qualitative approach, through the content analysis of the s ummaries and methodology of work, categorized according to the methods, approaches, tools and research techniques. Ninety seven on - line available dissertations were analyzed and allowed outline the characteristics of the studies prepared in PPGA / UCS. Thi s way, from the analyzed productions there is the predominance of qualitative approach and the use of the interview guide as a tool for data collection. Thus, these results demonstrate that the research conducted in the Master in Business Management mainly focus on the comprehension depth in the investigated phenomena.